2012
DOI: 10.4103/1319-3767.103427
|View full text |Cite
|
Sign up to set email alerts
|

Role of proteases and antiprotease in the etiology of chronic pancreatitis

Abstract: Background/Aim:Chronic pancreatitis (CP) is the progressive and irreversible destruction of the pancreas characterized by the permanent loss of endocrine and exocrine function. Trypsin, the most important digestive enzyme plays a central role in the regulation of all other digestive enzymes. Chymotrypsin, an endopeptidase hydrolyzes peptides at amino acids with aromatic side chains. Alpha-1-antitrypsin is a principal antiprotease which protects the mucosal tissue from the proteolytic effects of trypsin and chy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…[ 22 ] Ca 2+ -activated phosphatase and proteases are the targets of acinar cell Ca 2+ signaling generated during pancreatitis. [ 2 ] Calcineurin inhibitors can result in decreased zymogen activation. The first step of AP is characterized by Ca 2+ -mediated enzymatic activation, followed by a systemic inflammatory response as a second step.…”
Section: Premature Trypsinogen Activation In the Onset Of Pancreatitimentioning
confidence: 99%
See 4 more Smart Citations
“…[ 22 ] Ca 2+ -activated phosphatase and proteases are the targets of acinar cell Ca 2+ signaling generated during pancreatitis. [ 2 ] Calcineurin inhibitors can result in decreased zymogen activation. The first step of AP is characterized by Ca 2+ -mediated enzymatic activation, followed by a systemic inflammatory response as a second step.…”
Section: Premature Trypsinogen Activation In the Onset Of Pancreatitimentioning
confidence: 99%
“…[ 34 ] Inflammatory responses inhibit apoptosis during acute pancreatitis. [ 2 ] A study has shown that neutrophils play a role in the pathologic activation of digestive enzymes in AP through NADPH-oxidase dependent way. [ 35 ] Intrapancreatic activation of trypsinogen may also induce NFκB signaling.…”
Section: Premature Trypsinogen Activation In the Onset Of Pancreatitimentioning
confidence: 99%
See 3 more Smart Citations